Making a difference? : social assessment policy and praxis and its emergence in China - Price, Susanna (Social development specialist); Robinson, Kathryn May, 1949- (Asia Pacific studies ;, 2015)
Social assessment for projects in China is an important emerging field. This collection of essays - from authors whose formative work has influenced the policies that shape practice in development-affected communities - locates recent Chinese experience of the development of social assessment practices (including in displacement and resettlement) in a historical and comparative perspective. Contributors - social scientists employed by international development banks, national government agencies, and sub-contracting groups - examine projects from a practitioner's perspective. Real-life experi.